If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + -47 = 105 + -3x Reorder the terms: -47 + 13x = 105 + -3x Solving -47 + 13x = 105 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -47 + 13x + 3x = 105 + -3x + 3x Combine like terms: 13x + 3x = 16x -47 + 16x = 105 + -3x + 3x Combine like terms: -3x + 3x = 0 -47 + 16x = 105 + 0 -47 + 16x = 105 Add '47' to each side of the equation. -47 + 47 + 16x = 105 + 47 Combine like terms: -47 + 47 = 0 0 + 16x = 105 + 47 16x = 105 + 47 Combine like terms: 105 + 47 = 152 16x = 152 Divide each side by '16'. x = 9.5 Simplifying x = 9.5
| X^(1/2)-7X^(1/4)+12=0 | | 8t-15=6t+11 | | n+1.8=3.0 | | 4.66=r-1/3 | | 5x+71=11x+12 | | Y+3=2x-5 | | 13x^2+11x^3+15x^2= | | -16t^2+14t+2=0 | | X^(1/2)-7X^(1/4)+12+0 | | 8m/2m | | 64t^2-16t+1=0 | | 1/3+1 | | 375x^3-192y^3= | | 5=9-x2 | | h=1/2.2h | | 58-5x=13x+16 | | 54-2x=16x+20 | | -3y=7x+6 | | 2y=8x+4 | | 3-7x+5.8-12x+18.2-x=2x+5 | | 2/1+x+5/1-x=16/1-x2 | | 2d^2-7d-5=0 | | 1.2(x-2)+0.5(1-x)=2.3 | | 2x-26=10x-70 | | 4x+3.5-1.5x=2.5-x | | (x-2)/3+(x-4)/5-(x-7)/6=(x-5)/2 | | 6x^2+8x-83=0 | | 1/k=x^2-x+1 | | 6x^2+8x-84=0 | | (1/2)(1-3x)-(2/3)(1-2x)=(1/4)(1+x)-(1/6)(1-x) | | -3x=-5+8 | | P-2/p+2=13 |